2021
DOI: 10.3390/healthcare9060733
|View full text |Cite
|
Sign up to set email alerts
|

Neuropsychiatric and Psychological Symptoms in Patients with Lyme Disease: A Study of 252 Patients

Abstract: This study examined the relationship between neuropsychiatric and psychological symptoms in patients with Lyme borreliosis. We collected data from an experimental group of 252 Lyme disease patients and a control group of 267 healthy individuals. The quality of life and sleep, attention and memory performance were assessed in both groups. Additionally, we investigated depressive symptoms in patients with Lyme disease to examine whether the duration of the disease had an influence on the severity of symptoms sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
(17 reference statements)
1
11
0
Order By: Relevance
“…Patients with a prior history of LD frequently reported an increase in depressive symptoms post infection. One study found that 68% of patients with a current or prior diagnosis of LD had Beck Depression Inventory (BDI) scores that met the criteria for clinical depression [ 12 ]. Interestingly, another study from Poland found that patients who were diagnosed with early B. burgdorferi infection through serological testing presented higher levels of depression and anxiety compared to patients with late infection [ 13 ].…”
Section: Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Patients with a prior history of LD frequently reported an increase in depressive symptoms post infection. One study found that 68% of patients with a current or prior diagnosis of LD had Beck Depression Inventory (BDI) scores that met the criteria for clinical depression [ 12 ]. Interestingly, another study from Poland found that patients who were diagnosed with early B. burgdorferi infection through serological testing presented higher levels of depression and anxiety compared to patients with late infection [ 13 ].…”
Section: Reviewmentioning
confidence: 99%
“…Out of 10 articles analyzed, five found that generalized cognitive decline was evident among LD patients who had neuroborreliosis [ 12 , 15 - 18 ]. In comparison to healthy control populations, LSLD patients displayed deficits in working memory, verbal learning/memory, non-verbal learning/memory, alertness, visuoconstructive, and frontal executive functions.…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…(Bransfield, 2018). Some behavioral changes have been observed, but they seem to be merely transient side effects of either current or recent Lyme disease (Makara-Studzinska et al, 2017; Hundersen et al, 2021; Tetens et al, 2021).…”
Section: Introductionmentioning
confidence: 99%